Students Narratives of Ethical Dilemmas and Professionalism Issues During a Rotation in Surgery - Gilles Beauchamp; Ramses Wassef; Bryn Williams-Jones (Canadian Journal of Bioethics, 2025)
Background: The education of medical students necessitates teaching not only the science of medicine but also the skills needed for ethical reflection and moral reasoning as well as professionalism. At the Université de Montréal, starting in 2004, third-year medical students were initiated to ethics and professionalism during a weekly seminar on clinical skills during their surgery rotation. Students had to recognize an ethical dilemma or a professionalism issue that occurred during the rotation and write a case narrative and reflection on the moral issue. Method: Student narratives describing ethical or professionalism incidents were collected between 2004 and 2020. These were analyzed to identify the moral challenges that students experienced, and how they reacted to ethical dilemmas or professionalism issues. Results: Of the 1145 narratives collected, 396 were coded as an ethical dilemma, subdivided into end-of-life decisions, decision for treatment, dilemmas concerning justice and resource allocation, and student educational dilemmas including relationships with residents. Professional issues were more frequently reported (n=749), subdivided into communication of bad news, professional behaviour and attitude, consent, confidentiality, truthful disclosure of sensitive results, errors, professional responsibility and commitment and relationships with colleagues. In 40% of narratives there was a positive opinion about the issues reported, while in 60% students felt the ethical decision or professional attitude or conduct was less than ideal. Conclusion: This seminar was an effective means for medical students to identify and discuss the ethical and professional issues experienced during their clerkship – issues regarding communication were the primary concern followed by professional behaviour. These narratives provide a good picture of the hidden curriculum; and they show that students can reflect meaningfully on issues concerning ethics and professionalism.